Percutaneous Onsite Insertion of Catheter for Peritoneal Dialysis - A New Method Introduction in the Country - Pushevski, Vladimir; Nikolov, Igor; Karagjozov, Pance; Darko DJambaz; Rambabova-Bushljetik, Irena (Walter de Gruyter GmbH, 2023)
Peritoneal dialysis (PD) is one of the options for renal replacement therapy (RRT) in the end stage renal disease (ESRD) patients. Compared to hemodialysis (HD), patients on PD experience a greater sense of well-being, an improved steady state in terms of extracellular fluid volume shifts and hemodynamics and it is preferred method for patients with problematic vascular access, bleeding tendencies, heart failure and elderly patients. In order to perform PD, a tunneled catheter should be placed through the abdominal wall and into peritoneal space, with positioning of the catheter within the most dependent portion of pelvis. Currently, there are several techniques available for PD catheter placement: open surgery, laparoscopic and percutaneous. We present for the first time in our country a case of 65 year old male patient to whom percutaneous onsite insertion of peritoneal catheter was performed. The idea is to emphasize that sometimes this should be a method of choice for RRT, especially in patients where general anesthesia should be avoid. Compared to other methods, percutaneous insertion is a simple procedure with no need for general anesthesia, and the benefits of quick recovery, earlier ambulation, and less delay in catheter placement.
Keywords: end stage renal disease; peritoneal dialysis; PD catheter; percutaneous insertion